Clinical characteristics of depressed children and adolescents with and without suicidal thoughts and behavior: a cross-sectional study - Häberling, I.; Preisig, M.; Emery, S.; Baumgartner, N.; Albermann, M.; Strumberger, M.; Schmeck, K.; Wöckel, L.; Erb, S.; Rhiner, B.; Contin, B.; Walitza, S.; et al. (Frontiers in Child and Adolescent Psychiatry, 2025)
IntroductionAbout half of all adolescents with major depressive disorder (MDD) have frequent suicidal thoughts and of those with suicidal ideations, about one-third attempt suicide. Identifying clinical characteristics associated with suicidal ideation and attempts is important for suicide prevention and clinical care.MethodsParticipants were four groups of adolescents diagnosed with MDD (n = 246, 180 females): (a) non-suicidal youths (n = 76), (b) ideators (n = 102; current suicidal ideation), (c) ideator-attempters (n = 56; current suicidal ideation and lifetime history of suicide attempt), and (d) lifetime attempters (n = 12; no current suicidal ideation but lifetime history of suicide attempt). Adolescents underwent clinical interviews and completed questionnaires assessing sociodemographic and clinical variables. Multivariate analyses of variance, logistic regression models, mediation and moderation analyses were run to assess which variables were associated with group membership.ResultsSuicidal ideators, irrespective of whether they had attempted suicide previously, had higher depression severity, higher anxiety and lower resilience compared to non-ideators. Hopelessness was associated with greater odds of being a suicidal ideator (p < .001, OR = 1.18) or an ideator-attempter (p = 0.036, OR = 1.13) than a non-suicidal youth. Attempter-ideators engaged more often in self-harm behavior compared to ideators (p = 0.046, OR = 1.13) and non-suicidal youths (p < .001, OR = 1.45). Ideator-attempters had experienced more childhood maltreatment, with hopelessness mediating the relationship between childhood maltreatment and suicidal ideation. Self-harm moderated the relationship between suicidal ideation and the probability of having made a suicide attempt.LimitationsOnly cross-sectional data was included, and data was based mostly on self-report measures.ConclusionsSuicidal thoughts are associated with increases in hopelessness while suicide attempts are linked to non-suicidal self-harm behavior. Treatment of non-suicidal self-harm behavior might be an effective suicide prevention strategy in young people with depression.Clinical Trial Registrationwww.ClinicalTrials.gov, identifier (NCT03167307).